The Effect of Slaughter Age and Gender of Broiler Cobb Strain on Body Weight, Carcass Weight, and Carcass Percentage - Purnomo, Agus; Sudarisman, Sudarisman; Prihtiyantoro, Wahyu; Agustin, Citravia (State Islamic University of Sultan Syarif Kasim Riau, 2024)
Demand for chicken consumption in Indonesia tends to increase every year. Broiler chickens were slaughtered at short age than past years, recently about 4 to 6 weeks. Total of 28 to 42 day old broiler chicks were distributed to completely randomized design in factorial scheme (4,5 and 6 weeks old) and 2 (male and female). All of evaluated were live body weight (LBW), carcass weight (CW), and carcass percentage (CP). Analyzed used Two Way analysis of variane (ANOVA) using SPSS with 5 replication. Duncan Multiple Range Test (DMRT) to determine the differences among treatment means. The result showed that live body weight had unsignificantly effect of sex but affect (P<0.05) to slaughter age (4, 5 and 6 weeks) it was 1460 g, 1881 g and 2310 g. The means of carcass weight with different sex of male and female had unsignificantly effect it was 1.283 g and 1.223, so do the carcass percentage was 69.43 % and 70.15%. This research can be concluded that difference sexing un affect to body weight (1.891 g), carcass weight (1.253 g) and carcass percentage (69.79%), but the female broiler get higher than male broiler. Thus slaughter age affect (P<0.05) to body weight, carcass weight and carcass percentage, at 4 weeks old was tend to decrease but increasily at 5 weeks and 6 weeks old. The best body weight, carcass weight and carcaas percentage at 5 weeks old, according to market demand.